Synthesis, fluorescence and two-photon absorption properties of push-pull 5-aryl[3,2-b]thienothiophene derivatives - Raposo, M. Manuela M. (2016)
Three series of novel push-pull 5-aryl[3,2-b]thienothiophene derivatives functionalized with potent electron-withdrawing terminal moieties) were synthesized in moderate to excellent yields through Suzuki coupling followed by Knoevenagel condensation. These novel chromophores combine intense absorption in the near-UV down to the orange visible region in relation with a strong intramolecular charge transfer transition. By combining strong donor and acceptor, large fluorescence quantum yield are achieved as well as large two-photon absorption responses. Interestingly, due to the improved rigidity and electronic delocalization provided by the thienothiophene moiety (compared to the bis-thiophene one) larger one- and two-photon brightness values are achieved. As a result, a library of new fluorescent dyes showing enhanced brightness (up to and tunable fluorescence (ranging from blue to the NIR region) has been obtained which offer interesting promises for bioimaging applications.